PENGARUH MOTIVASI DAN PERSEPSI ATAS GAYA BELAJAR SECARA BERSAMA-SAMA TERHADAP HASIL BELAJAR - aspari aspari aspari (Wanastra: Jurnal Bahasa dan Sastra, 2016)
Abstract - The goal of this research is to get data about the effect of motivation and perception to learning style in together to achievement of learning at Junior High School in Pamulang Tangerang Selatan. This research uses research method with correlation and regration analysis. It is mean, making connection  between data that tells about motivation and preception to learning style in together to learning achievment.The data about motivation and perception to learning style in together to learning achievment could be got over questioner by resercher with measuring something that has connection to: (1) there are effects of learning motivation signficantly and perception to learning style of studetns in together to achievment of learning. It can be known from the getting score of Fo=9,109 and Sig.0,000 < 0,05. In together, the variable of learning motivation and perception to learning style of students gave contribution 24,2% to the variable of learning achievment in english. (2) There are effects of learning motivation significantly to English learning achievment. It can be known from the getting score of thitung =2,214 and Sig. 0,031 < 0,05. The variable of learning motivation contrbuted 12,67% in increasing English learning achievment. (3) There are effects of perception to studetns learning style to students learning achievment significantly. It can be known by the getting score of thitung = 2,061 and Sig. 0,044 < 0,05. The variable of perception to studetns learning style contributed 11,53% in increasing English Learning achievment. It tells us that there are possitive effects and significant to learning motivation and perception in learning style to student learning achievment.